Perancangan Desain Ergonomi di Ruang Rekam Medis Klinik Mitra Keluarga Sejahtera - Arifani, Elian Nanda; Ardianto, Efri Tri; Santi, Maya Weka; Alfiansyah, Gamasiano (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The medical record room should meet ergonomic aspects, so research is needed that aims to make an ergonomic design in the medical record room. The room consists of a patient registration unit, filing rack and nurse station, using non-ergonomic plastic chairs and a lack of filing shelves to accommodate inpatient medical record files. This type of research was a qualitative study, data collected through observation, interviews, documentation studies and brainstorming. The results of the study indicate that it was necessary to design a new medical record work unit room that was adapted to the flow of medical record file processing, design of tables, chairs and filing racks that are adapted to the anthropometry of officers. The results of the new design of the medical record work unit measuring 4 m x 4 m, the design of the table and chairs and filing racks which had been adjusted to standards or theory using the SketchUp 3D 2020 application, in accordance with ergonomic aspects which include efficiency, health, safety, security and comfort.Keywords: design; ergonomics; medical records ABSTRAK Ruang rekam medis seharusnya memenuhi aspek ergonomic, maka diperlukan penelitian yang bertujuan untuk membuat desain ergonomi di ruang rekam medis. Ruang tersebut terdiri dari unit pendaftaran pasien, rak filing dan nurse station, menggunakan kursi plastik yang tidak ergonomis serta kurangnya rak filing untuk menampung berkas rekam medis rawat inap. Jenis penelitian ini adalah studi kualitatif, data dikumpulkan melalui observasi, wawancara, studi dokumentasi dan brainstorming. Hasil penelitian menunjukkan bahwa perlu adanya desain ruang unit kerja rekam medis baru yang disesuaikan dengan alur pengolahan berkas rekam medis, desain meja, kursi dan rak  filing yang disesuaikan dengan antropometri petugas. Hasil desain baru ruang unit kerja rekam medis berukuran 4 m x 4 m, desain meja kursi dan rak filing yang sudah disesuaikan dengan standar atau teori dengan menggunakan aplikasi SketchUp 3D 2020, sesuai dengan aspek ergonomi yang meliputi efisiensi, kesehatan, keselamatan, kemanan dan kenyamanan.Kata kunci: desain; ergonomi; rekam medis